If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1-x+3x=-2(x+1)
We move all terms to the left:
1-x+3x-(-2(x+1))=0
We add all the numbers together, and all the variables
2x-(-2(x+1))+1=0
We calculate terms in parentheses: -(-2(x+1)), so:We get rid of parentheses
-2(x+1)
We multiply parentheses
-2x-2
Back to the equation:
-(-2x-2)
2x+2x+2+1=0
We add all the numbers together, and all the variables
4x+3=0
We move all terms containing x to the left, all other terms to the right
4x=-3
x=-3/4
x=-3/4
| 2x^{2}-14x-13=0 | | √x^2=√687 | | 2*5^x=50 | | 12x-15=6-3x* | | 3(y+3)-y=17 | | -3.8w+4=4.4w-37 | | 50+2x-5=180 | | 26{x+3}=26+3 | | 10=4−3x | | y=⅗×⁵ | | -20y=-250.8 | | (12x-10)=(10x+10) | | 533=-0.04x+20 | | 2.7=i÷0.4 | | y+9=2.10+18.90 | | 5+5x+5(x+4)=31+4 | | 0.4*(1+5x)^0.5=4-x | | n+11=–7 | | X+y+2×=31 | | g+18=9 | | 4x+25+75=180 | | 9x+7=10×-10 | | 4x+15=21-x | | 4x=25=75 | | a2−8a+12=0 | | u−–11=16 | | 5=9-9/q | | z+(6.4÷4)=9.6 | | -6(-3x+7)=2(7x+5) | | 2.6875x=360 | | 5r+6+3r=3+5r | | x2–4x+3=0 |